Ø£Ø¨Ùˆ Ø¨ÙƒØ± Ø§Ù„Ø¯Ù…ÙŠØ§Ø·ÙŠ Ø§Ù„Ø´Ø§ÙØ¹ÙŠ Ø§Ù„ØªØ¹Ø±ÙŠÙ Ø¨Ù‡ ÙˆØ¨ÙŠØ§Ù† Ù…Ù†Ù‡Ø¬Ù‡ Ø§Ù„ØØ¯ÙŠØ«ÙŠ ÙÙŠ ÙƒØªØ§Ø¨Ù‡ (Ø¥Ø¹Ø§Ù†Ø© Ø§Ù„Ø·Ø§Ù„Ø¨ÙŠÙ†) - Hakim Sudahnan, Lukmanul (Ø§Ù„Ø¨ØµÙŠØ±Ø©: Ù…Ø¬Ù„Ø© Ø§Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ©, 2020)
The book I'aanatu ath-thaalibin 'alaa halli al-faazhi fathi al-mu'iin by Abu Bakr al-DimyÄthi al-SyÄfi'i is one of the most important books of fiqh in the Shafi'i school, the proof is that the book is a reference in local Islamic boarding schools and the main reference for muftis as well as a scientific reference for students in our country, Indonesia. Therefore, this study aimed to identify Abu Bakr al-Dimyathti al-Syafi'i, one of the Shafi'i scholars, and reveal his scientific personality in the science of hadith by studying his method of hadith, particularly in his book I'aanatu ath-thaalibin. This study employed an inductive deductive approach. The results of the research reveal that Abu Bakr al-Dimyathti al-Syafi'i is one of the phenomenal contemporary scholars of the Shafi'i school. In his book, he uses a lot of hadiths and atsar as arguments in establishing a law of fiqh without requiring the validity of these propositions, so that there are arguments that are authentic, fine, and weak. The depth of his knowledge in the field of hadith is evident in his book I'aanatu ath-thaalibin on the following points: the number of hadith cited that he used as the proposition, the number reached approximately one thousand three hundred and eighty-three (1383) hadith marfu' without repetition. His book also shows the depth of his understanding of the science of musthalah al-hadith. Among his method of inference in the hadiths is his excessive attention to the two sahih books in postulating until the number - according to my estimation - reaches around five hundred and sixty-three (563) hadiths, this is a fantastic number, besides he does not postulate weak hadiths and ones that are munkar.